Brain-targeted glycyrrhizic-acid-loaded surface decorated nanoparticles for treatment of cerebral ischaemia and its toxicity assessment. Issue 1 (4th December 2019) - Ahmad, Niyaz; Al-Subaie, Abeer M.; Ahmad, Rizwan; Sharma, Sonali; Alam, Md Aftab; Ashafaq, Mohammad; Abdur Rub, Rehan; Ahmad, Farhan Jalees
Abstract: Objective: Enhancement of CS-GA-PCL-NPs (Glycyrrhizic Acid-encapsulated-chitosan-coated-PCL-Nanoparticles) bioavailability in brain. Methods: Double emulsification solvent evaporation method in order to develop CS-PCL-NPs (Chitosan-coated-PCL-Nanoparticles) followed by characterization of particle size and distribution, zeta potential, encapsulation efficiency and drug release ( in vitro ). To determine drug-uptake and its pharmacokinetic profile in brain as well as plasma, UHPLC (triple quadrupole Q-trap) MS/MS method was developed and optimized for CS-GA-PCL-NPs as well as to follow-up examined effective role of optimized NPs in reduction of all brain injury parameters after MCAO through the grip strength, locomotor activity, inflammatory cytokines levels, measurement of infarction volume and histopathological changes in neurons with safety/toxicity after i.n. in animals. Results: The developed NPs showed an average particle size, entrapment efficiency with PDI (polydispersity index) of 201.3â€‰Â±â€‰4.6â€‰nm, 77.94â€‰Â±â€‰5.01% and 0.253â€‰Â±â€‰0.019, respectively. Higher mucoadhesive property for CS-GA-PCL-NPs as compared to conventional and homogenized nanoformulations was observed whereas an elution time of 0.37â€‰min and m/z of 821.49/113.41 for GA along with an elution time of 1.94â€‰min and m/z of 363.45/121.40 was observed for hydrocortisone i.e. Internal standard (IS). Similarly, %CV i.e. inter and intra assay i.e. 0.49â€"4.41%, linear dynamic range (10â€"2000â€‰ng/mL) and % accuracy of 90.00â€"99.09% was also observed. AUC0â€"24 with augmented Cmax was noted (** p â€‰<â€‰.01), in Wistar rat brain as compared to i.v. treated group during pharmacokinetics studies. In MCA-occluded rats, enhanced neurobehavioral activity i.e. locomotor and grip strength along with a decrease in cytokines level (TNF-Î± and IL-1Î²) was observed, following i.n. administration. Conclusions: CS-coated-GA-loaded-PCL-NPs when administered i.n. enhanced the bioavailability of the drug in rat brain as compared to i.v. administration. The observation from toxicity study concludes; the developed NPS are safe and free of any health associated risk. Abstract :